How TikTok Short-form Video Content Will Effect on Tourism Destination Visit Intention? The Role of Consumer Engagement, Consumer Involvement, and E-Wom - Ratu Salzabiella Arsya Maharani; Rifelly Dewi Astuti (PT Keberlanjutan Strategis Indonesia, 2026)
The development of short-form video-based social media has positioned TikTok as a strategic channel for tourism destination promotion because it can deliver visual experiences, information, and social validation quickly to prospective tourists. This study aims to analyze the effect of TikTok short-form video content value on visit intention toward Indonesian tourism destinations through the roles of consumer engagement, consumer involvement, and electronic word-of-mouth (eWOM). This study applies the Stimulus-Organism-Response (S-O-R) framework, with content characteristics as the stimulus, perceived value, consumer engagement, and consumer involvement as the organism, and eWOM and visit intention as the response. This study uses a quantitative explanatory approach through an online survey, and the data are analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The study involved 300 TikTok users in Indonesia who had been exposed to tourism destination video content, with respondents predominantly female, in the productive age group, and domiciled in Jabodetabek. The findings show that entertainment, informativeness, credibility, personalization, and irritation significantly influence perceived value, while incentives do not have a significant effect. The findings also reveal that perceived value positively influences consumer engagement, consumer involvement, and visit intention, while consumer engagement, consumer involvement, and eWOM contribute to increasing visit intention through psychological engagement and digital recommendation mechanisms. This study contributes theoretically by extending the application of the S-O-R framework to TikTok short-form video content in digital tourism marketing and managerially by providing implications for destination managers to design informative, credible, entertaining, personalized content that encourages user interaction and positive eWOM.